Acute kidney injury among adult patients with sepsis in a low-income country: clinical patterns and short-term outcomes - Bagasha, Peace; Nakwagala, Frederick; Kwizera, Arthur; Ssekasanvu, Emmanuel; Kalyesubula, Robert (BMC Nephrology, 2015)
Acute kidney injury (AKI) is a common complication of sepsis. We determined the prevalence of AKI among adult patients with sepsis on the medical wards in a low-income country and described their clinical pattern and outcomes at discharge. Methods: We conducted a cross-sectional study of sepsis-related AKI on the adult medical wards of Mulago National Referral Hospital between January and April 2013. All patients meeting the American College of Chest Physicians (ACP) sepsis criteria were recruited. Demographic, clinical, laboratory and ultrasonography data were recorded and all patients with AKI were followed up to a maximum of 2 weeks. Proportional analysis was carried out and odds ratios with 95% confidence intervals were calculated in the bivariate analysis. Results: Of 387 patients recruited, 217 (55.6%) were male and the average age was 37 years (range18–90 years). The prevalence of sepsis-related AKI was 16.3%. Age >59 years (p = 0.023), a postural drop in systolic blood pressure of >9 mmHg (p = 0.015) and a white blood cell count >12,000 cells/mL (p = 0.003) were significantly associated with AKI. In-hospital mortality among patients with AKI was 21% (13/63). 59% (20/49) of patients who were discharged alive or were still on the wards after 2 weeks had persistent kidney injury. Acute Kidney Injury Network (AKIN) Stage 3 was significantly associated with persistence of kidney injury (p = 0.001). None of the patients requiring dialysis or ICU care received either because of limited access. Conclusions: The prevalence, morbidity and mortality due to AKI among sepsis patients in Uganda is very high and limited access to dialysis and ICU care is a major factor in poor outcomes for these patients.
Keywords: Acute kidney injury; AKIN; Sepsis; Mortality; Resource-limited setting; Africa